2011
DOI: 10.1016/j.molcel.2011.12.008
|View full text |Cite
|
Sign up to set email alerts
|

The Little Elongation Complex Regulates Small Nuclear RNA Transcription

Abstract: SUMMARY Eleven-nineteen Lysine-rich Leukemia (ELL) participates in the Super Elongation Complex (SEC) with the Pol II CTD kinase P-TEFb. SEC is a key regulator in the expression of HOX genes in Mixed Lineage Leukemia (MLL) -based hematological malignancies, in the control of induced gene expression early in development, and in immediate early gene transcription. Here, we identify an SEC-like complex in Drosophila, as well as a distinct ELL-containing complex that lacks P-TEFb and other components of SEC named … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
96
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(105 citation statements)
references
References 59 publications
(91 reference statements)
7
96
1
Order By: Relevance
“…In this case, any factor that is important for both transcription and 39-end processing will not be scored. This likely explains why depletion of members of the snRNA activating protein complex (SNAPc) do not trigger GFP expression, nor did the members of the recently defined Little Elongation Complex (Hung and Stumph 2011;Smith et al 2011). Depletion of any of these factors would be predicted to extinguish U7-GFP promoter activity and would not result in GFP expression.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, any factor that is important for both transcription and 39-end processing will not be scored. This likely explains why depletion of members of the snRNA activating protein complex (SNAPc) do not trigger GFP expression, nor did the members of the recently defined Little Elongation Complex (Hung and Stumph 2011;Smith et al 2011). Depletion of any of these factors would be predicted to extinguish U7-GFP promoter activity and would not result in GFP expression.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA pol II (RPB1) ChIP-Seq data (reads and binding sites) were downloaded from NCBI GEO (GSE32120) 70 . Binding sites were annotated as described above.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that two ELL/EAF-containing complexes, super elongation complex (SEC) and little elongation complex (LEC), specifically regulate the transcription of distinct genes [4,5]. LEC is composed of multiple subunits including the ELL/EAF component, KIAA0947, NARG2 and ZC3H8 [3,6,7].…”
Section: Transcription Elongation Factors Including Eleven Lysine-ricmentioning
confidence: 99%
“…LEC is composed of multiple subunits including the ELL/EAF component, KIAA0947, NARG2 and ZC3H8 [3,6,7]. KIAA0947 and NARG2 were also known as ICE1 and ICE2 (interacts with C-terminus of ELL subunits 1 and 2), respectively [4]. It has been shown that LEC plays an essential role in transcription of small nuclear RNA (snRNA) genes.…”
Section: Transcription Elongation Factors Including Eleven Lysine-ricmentioning
confidence: 99%